2015
DOI: 10.2174/1381612821666150122123748
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Advances of Matrine and Its Derivatives

Abstract: As the second leading cause of death in the world, the total number caused by cancer in 2008 is 1.4 million. The great cancer incidence worldwide increases the search for new, safer and efficient anticancer agents (especially to find the new structures and more active anticancer drugs from the natural products) aiming the prevention or the cure of such illness. For a century, matrine (an alkaloid isolated from sophorae flavescens Ait.) has been widely studied in the field of cancer. This review briefly describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Modern research has also shown various pharmacological effects of Alkaloids of Sophora flavescens (ASF), such as antimicrobial, antiinflammatory, anti-allergic, anti-tumor, anti-arrhythmia, anti-hepatitis, and regulation of the immune system [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Among many chemical components from the ASF, quinolizidine alkaloids such as matrine (MT), sophoridine (SPR) and oxymatrine (OMT) have been demonstrated to be important active compounds [18][19][20][21][22][23][24][25][26][27][28][29]. The quality of ASF as herbal medicine is typically evaluated and controlled by the total alkaloid content.…”
Section: Introductionmentioning
confidence: 99%
“…Modern research has also shown various pharmacological effects of Alkaloids of Sophora flavescens (ASF), such as antimicrobial, antiinflammatory, anti-allergic, anti-tumor, anti-arrhythmia, anti-hepatitis, and regulation of the immune system [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Among many chemical components from the ASF, quinolizidine alkaloids such as matrine (MT), sophoridine (SPR) and oxymatrine (OMT) have been demonstrated to be important active compounds [18][19][20][21][22][23][24][25][26][27][28][29]. The quality of ASF as herbal medicine is typically evaluated and controlled by the total alkaloid content.…”
Section: Introductionmentioning
confidence: 99%
“…Therapies aimed at inducing apoptosis of RA-FLS could be valuable for RA treatment 5, 43 . The anti-cancer and apoptosis-inducing properties of matrine are well documented 10, 12, 44, 45 . A previous study investigated the effects of MASM on rat hepatocytes and hepatic stellate cells (HSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Matrine is an active alkaloid compound that is isolated from the traditional Chinese herb Sophora flavescens and has a wide spectrum of biological properties, such as anti-inflammatory 68 , antiviral 9 , anti-cancer 1012 , anti-fibrotic 13 and anti-dementia 14 properties. However, until now matrine has not been developed into a drug because of its low therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low water solubility, bioavailability and bioactivity of matrine, coupled with its considerable side effects, which include general toxicity to the central nervous system, have limited its utility as a therapeutic drug (17,18). Therefore, studies have been focusing on developing derivatives and analogues of matrine by total synthesis or structural modifications in order to improve its activity and bioavailability (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…However, the low water solubility, bioavailability and bioactivity of matrine, coupled with its considerable side effects, which include general toxicity to the central nervous system, have limited its utility as a therapeutic drug (17,18). Therefore, studies have been focusing on developing derivatives and analogues of matrine by total synthesis or structural modifications in order to improve its activity and bioavailability (19)(20)(21).A previous study demonstrated that the amide bond may be required for the antitumor activities of matrine as following opening of the D-ring and breaking of the amide bond, the anti-proliferative activities of matrine are lost (22). Based on the potential positions for modifying matrine, the present study designed, synthesized and characterized five matrine derivatives for their anti-proliferation potential.…”
mentioning
confidence: 99%